Christian beliefs and values in science and religious education: an essay to assist the work of teachers of both subjects - Black, Paul (International studies in Catholic education, 2017)
Teachers, both of science and of religion, have to help pupils to learn about the links between these subjects. An effective way to support this learning should start from the beliefs and ideas that pupils already have, ideas which might well be influenced by public debates, often characterised by controversy, between those holding strong beliefs about the two areas. This article aims to give teachers a framework of information and argument to guide their design of teaching in this overlap area. In the first of three main sections, there is a summary account of the history of the science-religion relationships, showing that over the last two millennia they have oscillated between positive support and negative controversy. A second section analyses this history in terms of three models of the relationship. One is a model of conflict in which each disputes the knowledge claims of the other. Another is one of mutual independence in which each accepts to work within its side of an agreed boundary. Finally, there is a model of collaboration, in which each discerns positive contributions that the other can make to its own insights. The third main section discusses the implications of the preceding analyses for curriculum and pedagogy in both science education and religious education, with a stress on the similarity between the pedagogic aims and values to which teachers of both subjects should work.